2022
DOI: 10.3390/su14031427
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Efficient Irrigation of Urban Landscapes: Analysis Using Remote Sensing, Parcel Data, Water Use, and Tiered Rates

Abstract: To understand how landscape irrigation can be better managed, we selected two urban irrigation systems in northern Utah, USA, and performed a statistical analysis of relationships among water use, irrigated area, plant health (based on the Normalized Difference Vegetation Index), and water rate structures across thousands of parcels. Our approach combined remote sensing with 4-band imagery and on-site measurements from water meters. We present five key findings that can lead to more efficient irrigation practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Second, the typical components of residential sprinkler systems are too imprecise. The physical layout of residential landscapes-the engineered part-often results in small, irregular, isolated areas such as park strips (between the road and the sidewalk) and flower beds (Figure 2) that are difficult to cover efficiently with standard sprinkler heads [5,9]. Second, the typical components of residential sprinkler systems are too imprecise.…”
Section: The Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the typical components of residential sprinkler systems are too imprecise. The physical layout of residential landscapes-the engineered part-often results in small, irregular, isolated areas such as park strips (between the road and the sidewalk) and flower beds (Figure 2) that are difficult to cover efficiently with standard sprinkler heads [5,9]. Second, the typical components of residential sprinkler systems are too imprecise.…”
Section: The Problemmentioning
confidence: 99%
“…Finally, customers, as a group, are too untrained. Several studies document that many customers overwater landscapes due to the lack of adequate irrigation training, skills, and knowledge [3,5,11]. While a few are well informed, most know little of plant, soil, and water science, yet millions of them make daily decisions about how to use water resources.…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Because consumptive water use is the culprit [5,6], we need strategies to reduce consumptive water use upstream-ideally without losing the intended benefits-and leave more water available for the lake. One prime candidate is residential landscape irrigation, which recent studies show can be done far more efficiently even without changing the landscapes [9,10]; another is agricultural irrigation, where Utah has a well-funded program for water optimization [11,12]. Utah has had water conservation goals since 2000, and a 2019 update revised them to capture new technologies, policies, and regionally specific opportunities [13].…”
Section: The Transformationmentioning
confidence: 99%
“…More studies have shown the efficiency of applying the LoS concept in different areas such as Shurtz, et al [15], in exploring water use for irrigation in urban settings and the role of pricing in encouraging users to match their water use to the LoS, or Atwater, et al [16], in suggesting an individualized approach to determining water rates based on customers' water-use patterns using smart meters, and Han, et al [17], in recommending the use of customer-driven LoS to set appropriate service levels in water infrastructure asset management. In Australia, rural water prices are determined based on the cost of supply as "cost reflective pricing" and crucially reflecting the LoS provided [18].…”
Section: Introductionmentioning
confidence: 99%